5x-x+12+2x-7=10

Simple and best practice solution for 5x-x+12+2x-7=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-x+12+2x-7=10 equation:


Simplifying
5x + -1x + 12 + 2x + -7 = 10

Reorder the terms:
12 + -7 + 5x + -1x + 2x = 10

Combine like terms: 12 + -7 = 5
5 + 5x + -1x + 2x = 10

Combine like terms: 5x + -1x = 4x
5 + 4x + 2x = 10

Combine like terms: 4x + 2x = 6x
5 + 6x = 10

Solving
5 + 6x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 6x = 10 + -5

Combine like terms: 5 + -5 = 0
0 + 6x = 10 + -5
6x = 10 + -5

Combine like terms: 10 + -5 = 5
6x = 5

Divide each side by '6'.
x = 0.8333333333

Simplifying
x = 0.8333333333

 

See similar equations:

| 7g=4g-21 | | -6x+3=21 | | 9P=3p-18 | | 2x^2+9x+6=0 | | 6x-92=x+3 | | 7u=5u-20 | | 4x-19=3-7x | | 3x^2+12x-36=0 | | 9p+8=10p+7 | | 2-8=-6 | | 5(2x-3)-6x=9 | | -9=3(-2) | | -18=3(-8) | | -3=3(-8) | | -30=3(-10) | | (11x+2)+(6x+4)+(x+5)=90 | | 2x-17=13-3x | | 4(37)= | | 11+-2x=31+-7x | | 6(2x+2)=3x+2-2x | | 6r+2(3r-4)=16r+4 | | 3y+3y+4=1 | | 3x-8=8-x | | 3x+18y=15 | | 14x-5=135 | | 6(4y+4)=4(4y+3) | | 8z-5z+4=-3 | | 7(3m)-18+2m= | | .25(5b+11)=19 | | 9(22+3)=4(z+2) | | 14x-10=3(4+x) | | 2.17+3f=14 | | 10=8-3z | | 4-6(2y-2)=3y-4y | | 23ab-(-2ab)= | | (-17)(-2)= | | 10x+4=3x+5 | | 8x+11-3x=2x+2 | | 3x+(-7x)+x-10x= | | 9m-3=-51+m | | 24+y=123 | | 7x+4=4x+5 | | 7=a-91 | | 66.66b+9=-15 | | 72.9=8.1a | | 124=4x+6x+4 | | 2t-5t=9 | | x+4.02=2 | | 6x=5-17 | | x+5.01=4 | | x+29.25=38.68 | | 43-6(-3e)-5e= | | 4x+3-2x=-21 | | 8x=30-6 | | 6.5d+7=-6 | | 23=x+25 | | -8=8(y+3) | | 5+6a=41 | | 5x*(6y-3)=22 | | 15=3m-8m | | 7(2W-3)-5(3W-1)=0 | | -6+4x=5x | | -6=(2y+1) | | -7=7(y+2) | | 4x-5y=10 |